Teacher Managerial Strategy in Building Character Education During The Covid-19 Pandemic - Hijrawatil Aswat; Khaerun Nisa Tayibu; Satriawati (CV. Eureka Murakabi Abadi, 2022)
This research aims to analyze various managerial strategies of teachers in instilling character education in children during the Covid-19 pandemic. Research methods of literature review by looking for theoretical references relevant to the case or problem found, namely the managerial strategy of the teacher in strengthening character with the aim as a consideration in choosing and determining the appropriate strategy to use in accordance with its effectiveness and the ability of the teacher to implement it. The results showed that some of the managerial strategies of teachers in strengthening character education are to choose various methods applied online and offline. Online character strengthening activities include the involvement of various innovations in online learning methods through various interesting content, interactive multimedia courseware, portfolios, whatsapp class groups, google classes, sevima delink, virtual applications such as zoom meeting, google meeting, local live TV, Youtube, social media management, e-learning system management, character control books (chacker characters), Character games, establishing intense communication over seluller phones. As conclusion that character strengthening that can be done offline is home visit, raport character, school on a certain day, curricular, extracurricular and co-curricular activities listed in the vision and mission of the curriculum, routine activities in school order, spontaneous activities in the rules, planned activities in school programs, transparency contained in the school order and report card and development of organizational activities.